Domesticated honey bees evolutionarily reduce flower nectar volume in a Tibetan lotus. Issue 11 (1st November 2014) - Mu, Junpeng; Peng, Youhong; Xi, Xinqiang; Wu, Xinwei; Griffin, John N.; Niklas, Karl J.; Sun, Shucun
Abstract : Plants have evolved costly flowering traits, including the provisioning of rich nectar, to attract and reward their pollinators. Beekeeping (apiculture) locally increases densities of honey bees, which might drive economization of pollinator‐attracting traits, but the potential evolutionary consequences of beekeeping on plant–pollinator interactions remain unknown. Here, we present evidence suggesting that intensive apiculture has driven the rapid evolution of plant traits in the alpine lotus ( Saussurea nigrescens ) on the Tibetan Plateau by allowing reduced nectar volume provisioning without compromising pollination success. This conclusion is supported by measurements of reproductive and vegetative traits, including nectar, at sites of varying distance from apiaries that have housed introduced honey bees ( Apis mellifera ) since the early 1980s. Nectar volume was more than 60% lower at sites close to apiaries than at more distant sites, while nectar concentration remained consistent. When seedlings from field sites were grown under common garden conditions, trends in nectar volume identical to those in the field were observed, indicating that recently evolved genetic differences likely underlie patterns observed in the field. The adaptive advantage of reduced nectar volume under high pollinator density was clear in both the field and in the common garden. Specifically, plants from sites close to apiaries were taller, had more aboveground biomass, and produced more flowers and seeds compared to those at distant sites, which is consistent with the tradeoffs between nectar volume per flower and flower number per inflorescence within sites. The evolution of reduced nectar volume suggested by our results shows that the widespread practice of beekeeping might be a strong selective agent acting on wild plant populations and illustrates that human activities may indirectly affect evolution by changing critical species interactions.